The Effect of Paracetamol and Codeine Analgesic Combination on Creatinine Levels in Male Wistar Rats - Vianney Natasaputra; Taufik Eko Nugroho (Diponegoro International Medical Journal, 2020)
Background :  Pain is one of the most common complaint in patients. Combination of paracetamol and codeine is an alternative analgesic combination in chronic pain management. They belong to different group of analgesic and have different mechanism of action. Combination of these drugs give a better potential in pain management.  However, these drugs also have potential side effect on the kidney.Methods : An experimental study of post-test only control group design. The sample were 20 Wistar rats, randomized into 4 groups: control group, a group receiving paracetamol 32 mg/kg body weight, a group receiving codeine 1,9 mg/kg body weight, and a group receiving paracetamol 32 mg/kg body weight and codeine 1,9 mg combination, administered 4 times a day orally using gastric instillation for 28 days. At the 29th day, blood is collected from retro orbital vessel to measure the serum creatinine levels. Statistical analysis was conducted using ANOVA TestResult : Obtained from statistical analysis there is no significant difference in serum creatinine levels in Wistar rats given all treatment group (p > 0,05).Conclusion : There is no significant difference in serum creatinine levels between administration of paracetamol and codeine combination compared to the control group.